2015
DOI: 10.1007/s13744-015-0342-1
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Fluctuating Asymmetry and Herbivory of Tibouchina heteromalla in Restored and Natural Environments

Abstract: Fluctuating asymmetry (FA) is a parameter to measure developmental stability in plants, which can be altered by disturbances, pollution, and biotic factors such as herbivory. We evaluated the effects of environmental stress and herbivory on the FA levels in individuals of Tibouchina heteromalla (Melastomataceae) that occur in natural and undergoing restoration areas in rupestrian grasslands at Serra do Cipó, Brasil. Individuals were collected and measured in seven restored and five natural areas, totalizing 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Many researchers have explored correlations between average levels of leaf FA (based on 10–20 leaves per plant) and different indices of insect herbivory. These observational studies did not reach an agreed conclusion; some of them reported higher herbivory on plants with higher FA [ 5 , 6 , 7 ], while others discovered the opposite pattern [ 8 ], or reported the absence of any correlation between plant FA and herbivory [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have explored correlations between average levels of leaf FA (based on 10–20 leaves per plant) and different indices of insect herbivory. These observational studies did not reach an agreed conclusion; some of them reported higher herbivory on plants with higher FA [ 5 , 6 , 7 ], while others discovered the opposite pattern [ 8 ], or reported the absence of any correlation between plant FA and herbivory [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%